2023
DOI: 10.3389/fpsyt.2023.1243619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of internet addiction and academic satisfaction on mental health among college students after the lifting of COVID-19 restrictions in China

Ai-Ping Deng,
Cong Wang,
Jia Cai
et al.

Abstract: BackgroundInternet addiction (IA) among students, worsened by Coronavirus disease 2019 (COVID-19) pandemic, has become a social problem with the digitalization of school learning and many aspects of daily life. However, few studies on IA have been conducted among students after the lifting of COVID-19 restrictions in China.MethodThis large-sample, cross-sectional, online survey was conducted to explore the characteristics of IA and the association among IA, academic satisfaction, and mental health problems fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The Internet studies have also changed the focus from looking at the internet as a technological marvel to documenting the internet users and then to the analysis, the ages 10, 5 and 0 Years ago (Wellman 2004). Additionally, the Internet grati cations have been seen to develop a variety of mental health problems including Internet addiction (Dhir, et al 2015, Song, et al 2004, Song 2003) which usually results in compromising with the academic performance of an individual as reported by Nagarjappa (2023), Zubair (2023), Deng et al (2023) Fard (2022), Dou and Shek (2021), Ali, et al, (2019) thereby is a matter of great concern for the academicians and the researchers. So it is important to understand why people engage in different types of internet usage behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet studies have also changed the focus from looking at the internet as a technological marvel to documenting the internet users and then to the analysis, the ages 10, 5 and 0 Years ago (Wellman 2004). Additionally, the Internet grati cations have been seen to develop a variety of mental health problems including Internet addiction (Dhir, et al 2015, Song, et al 2004, Song 2003) which usually results in compromising with the academic performance of an individual as reported by Nagarjappa (2023), Zubair (2023), Deng et al (2023) Fard (2022), Dou and Shek (2021), Ali, et al, (2019) thereby is a matter of great concern for the academicians and the researchers. So it is important to understand why people engage in different types of internet usage behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In the second phase, Song et al ( 17 ) explored the relationship between academic performance and mental health status after lifting restrictions, indicating that college students’ mental health continued to be affected by COVID-19 during this phase. Deng et al ( 18 ) examined the relationship between internet addiction and mental health issues among college students after the lifting of restrictions, highlighting the need for establishing corresponding social intervention measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the influences of COVID-19 on China have been reported to continue with some pandemic-related changes in the culture ( 8 ); and even after the lifting of restrictive measures the widespread circulation of the virus caused new losses, anxiety ( 9 ), and ongoing public health concerns throughout, 2023 ( 10 ). In this post-COVID-19 era, research in China revealed that mental health problems related to the pandemic among university students persisted and demanded serious attention ( 11 ). Because COVID imposed mental stress and illness, it is important to seek to understand whether some students have the personality traits needed to help them adjust adequately to different local conditions.…”
Section: Introductionmentioning
confidence: 99%